A COMPARISON OF ADVERTISING VALUE AND ADVERTISING CREDIBILITY BETWEEN NATIVE ADVERTSING AND ADVERTORIAL - Nguyen, Tuyen (2016)
Nowadays, there are so many digital advertising buzzwords and technical jargons tossed around by industry professionals. Indeed, the huge amount of techniques, which are invented recently, exceedingly make marketing practitioners confused when building their online strategy. The reason is that they cannot be confident about how Internet users process these new formats, along with which one is the best option for their campaigns. Native advertising is a case in point. Given as a new approach in cooperating between advertisers and online publishers but the understandings of the concept are extremely sparse in previous literatures and academic theories. Most of marketing professionals still consider it as a digital version of the old practice - advertorial. Thus, this article focuses on the reactions toward the two types of sponsored content, namely native advertising and advertorial, to examine whether or not there are differences in consumer attitudes which are triggered by various differences in editorial characteristics. A survey among students (N=50) were conducted for only news website. The result implied that native advertising generates more appreciation and trust in readers’ perception. Specifically, consumers tend to perceive the native format as more amusing, more credible and less irritating than the traditional advertorial. Furthermore, two dimensions of persuasive knowledge, including advertising recognition and understanding persuasive intent were found to have significant influences on the responses of Internet users toward the two techniques in negative ways. Also, the study indicates that consumers seem to enjoy the content with the lower commercial sense in native ads, rather than pure advertorials. Finally, the key finding is the more consumers believe in an advert, the more they appreciate it. Eventually, implications for advertising and policy-makers are also in discussion. Native content appears to be a promising approach for advertisers and publishers. To increase the value of online advertising, the content of sponsored advertising should be cautiously prepared in order to satisfy audience expectations when experiencing in the news website environment. In addition, this study suggests advertisers minimizing the appearance of brand as well as hiding commercial purposes when communicating with audiences in order to reduce recognition, perceived selling intent, commercial senses and then to build consumers’ trust in the Internet.